2005
DOI: 10.1074/jbc.m410613200
|View full text |Cite
|
Sign up to set email alerts
|

DPP10 Modulates Kv4-mediated A-type Potassium Channels

Abstract: A new member of a family of proteins characterized by structural similarity to dipeptidyl peptidase (DPP) IV known as DPP10 was recently identified and linked to asthma susceptibility; however, the cellular functions of DPP10 are thus far unknown. DPP10 is highly homologous to subfamily member DPPX, which we previously reported as a modulator of Kv4-mediated A-type potassium channels (Nadal, M. S., Ozaita, A., Amarillo, Y., Vega-Saenz de Miera, E., Ma, Y., Mo, W., Goldberg, E. M., Misumi, Y., Ikehara, Y., Neub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
156
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(176 citation statements)
references
References 30 publications
(49 reference statements)
18
156
1
1
Order By: Relevance
“…These results suggest that the single transmembrane segment and the extracellular domains are important for the changes common to all DPP10s. This is consistent with findings by Zagha et al (2005), Ren et al (2005), and Li et al (2005) that showed the transmembrane domain and the surrounding region is sufficient for the DPL interaction with and the modulation of Kv4 channels. The extracellular domain of DPLs, based on C-terminal truncation studies, has been suggested to contribute in stabilizing the Kv4-DPL interaction (Zagha et al, 2005).…”
Section: Functional Roles Of Dpp10 Transmembrane and Extracellular Dosupporting
confidence: 81%
See 3 more Smart Citations
“…These results suggest that the single transmembrane segment and the extracellular domains are important for the changes common to all DPP10s. This is consistent with findings by Zagha et al (2005), Ren et al (2005), and Li et al (2005) that showed the transmembrane domain and the surrounding region is sufficient for the DPL interaction with and the modulation of Kv4 channels. The extracellular domain of DPLs, based on C-terminal truncation studies, has been suggested to contribute in stabilizing the Kv4-DPL interaction (Zagha et al, 2005).…”
Section: Functional Roles Of Dpp10 Transmembrane and Extracellular Dosupporting
confidence: 81%
“…This is consistent with findings by Zagha et al (2005), Ren et al (2005), and Li et al (2005) that showed the transmembrane domain and the surrounding region is sufficient for the DPL interaction with and the modulation of Kv4 channels. The extracellular domain of DPLs, based on C-terminal truncation studies, has been suggested to contribute in stabilizing the Kv4-DPL interaction (Zagha et al, 2005). Our lab also has observed that, upon cMyc-tagging of the DPP10 distal C-terminus, the coimmunoprecipitation between DPP10 and Kv4.2 is diminished, consistent with role of the extracellular domain in complex stabilization (H Jerng, unpublished observations).…”
Section: Functional Roles Of Dpp10 Transmembrane and Extracellular Dosupporting
confidence: 81%
See 2 more Smart Citations
“…These channels are formed by four Kv4 ␣ subunits in association with cytoplasmic KChIP (An et al, 2000;Rhodes et al, 2004) and/or transmembrane DPPX (Nadal et al, 2003) or dipeptidylpeptidase 10 (Jerng et al, 2004a;Zagha et al, 2005) auxiliary subunits. Coexpression of KChIP1-KChIP3, but not KChIP4, with Kv4 ␣ subunits in heterologous cells dramatically increases surface expression and slows the turnover rate of Kv4 protein, and slows the inactivation kinetics and speeds the rate of recovery from inactivation of Kv4 channels (An et al, 2000;Shibata et al, 2003;Jerng et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%